A multimodal international collaborative clinical research training program in China. Issue 1 (1st January 2019) - Zhang, Qian; Shi, Yu; Xin, Youqing; Zhang, Shutian; Zeng, Na; Liu, Mo; Wu, Shanshan; Wei, Wei; Li, Min; You, Hong; Jia, Jidong; Kong, Yuanyuan; et al.
ABSTRACT: Background : There is a strong need to include training of research methods in training programs for physicians. International clinical research training programs (CRTP) that comprehensively introduce the methodology of clinical research and combined with practice should be a priority. However, few studies have reported a multimodal international CRTP that provides clinicians with an introduction to the quantitative and methodological principles of clinical research. Objective : This manuscript is intended to comprehensively describe the development process and the structure of this multimodal training program. Methods : The CRTP was comprised of three distinct, sequential learning components: part 1 – a six-week online eLearning self-study; part 2 – a series of three weekly interactive synchronous webinars conducted between Durham, North Carolina, USA and Beijing, China; and part 3 – a five-day in-person workshop held at Beijing Friendship Hospital, Capital Medical University (BFH-CMU). Self-assessment quiz scores and participation rates were used to evaluate effectiveness of the training program. Participants' demographic characteristics, research experience, satisfaction and feedback on the program were collected using questionnaires. Results : A total of 50 participants joined the CRTP. Forty-four participants (88%) completed the program satisfaction questionnaires. The average quiz score of the six eLearning units varied from 31% to 73%. Among the three components of the program, the online eLearning self-study was felt to be the most challenging. Thirty-nine (89%) of the surveyed respondents were satisfied with all components of the training program. Among the respondents, 43 (98%) felt the training was helpful in preparing them for future clinical research projects and expressed willingness to recommend the program to other colleagues. Conclusions : We established a multimodal international collaborative training program. The program demonstrated acceptable participation rates and high satisfaction among Chinese clinicians. It provides a model that may be used by others developing similar international clinical research training programs for physicians.